Pengaruh Penggunaan Daring Unram Terhadap Motivasi dan Hasil Belajar Mahasiswa Pendidikan Matematika Selama Pandemi Covid-19 - Aliyatul Himmah; Amrullah Amrullah; Sripatmi Sripatmi; Sudi Prayitno (Griya Journal of Mathematics Education and Application, 2022)
This study aims to find out the effect of the use of Daring Unram on students’ learning motivation and learning outcomes in the Mathematics Education Study Program, University of Mataram. This type of research is causal comparative quantitative research (ex-post facto). The research population is Mathematics Education students class 2018, 2019, and 2020 who have studied online using Daring Unram in the even semester 2020/2021with a total of 419 people. Sampling uses a a cluster random sampling technique using the Slovin method so that there are 81 respondents for the study. The instrument in this study used a closed questionnaire with a Likert scale. Data were analyzed with the help of SPSS version 21. The results showed that: (1) There is a significant effect of the use of Daring Unram on students’ learning motivation with a value of . Furthermore, determination analysis is performed to see the magnitude of the infuence given by the use of Daring Unram on students’ learning motivation and obtained an R Square value of 0.239. This value means that the contribution given by the use of Daring Unram to students’ learning motivation is 23.9% with an enough relationship level; (2) There is a significant effect of the use of Daring Unram on students’ learning outcomes with a value of . Furthermore, determination analysis is performed to see the magnitude of the infuence given by the use of Daring Unram on students’ learning outcomes and obtained an R Square value of 0.270. This value means that the contribution given by the use of Daring Unram to students’ learning outcomes is 27% with an enough relationship level.